A new sphenodontian (Lepidosauria: Rhynchocephalia) from the Late Triassic of Argentina and the early origin of the herbivore opisthodontians - Martínez, Ricardo (2013)
Sphenodontians were a successful group of rhynchocephalian reptiles that dominated the fossil record of Lepidosauria during the Triassic and Jurassic. Although evidence of extinction is seen at the end of the Laurasian Early Cretaceous, they appeared to remain numerically abundant in South America until the end of the period. Most of the known Late Cretaceous record in South America is composed of opisthodontians, the herbivorous branch of Sphenodontia, whose oldest members were until recently reported to be from the Kimmeridgian?Tithonian (Late Jurassic). Here, we report a new sphenodontian, Sphenotitan leyesi gen. et sp. nov., collected from the Upper Triassic Quebrada del Barro Formation of northwestern Argentina. Phylogenetic analysis identifies Sphenotitan as a basal member of Opisthodontia, extending the known record of opisthodontians and the origin of herbivory in this group by 50 Myr.